Hierarchical hexagonal boron nitride nanowall–diamond nanorod heterostructures with enhanced optoelectronic performance. Issue 93 (20th September 2016) - Sankaran, Kamatchi Jothiramalingam; Hoang, Duc Quang; Korneychuk, Svetlana; Kunuku, Srinivasu; Thomas, Joseph Palathinkal; Pobedinskas, Paulius; Drijkoningen, Sien; Van Bael, Marlies K.; D'Haen, Jan; Verbeeck, Johan; Leou, Keh-Chyang; Leung, Kam Tong; et al.
Abstract : Covering diamond nanorod with hexagonal boron nitride nanowalls is an effective approach for the fabrication of hierarchical heterostructured field emission devices that open new prospects in flat panel displays and high brightness electron sources. Abstract : A superior field electron emission (FEE) source made from a hierarchical heterostructure, where two-dimensional hexagonal boron nitride (hBN) nanowalls were coated on one-dimensional diamond nanorods (DNRs), is fabricated using a simple and scalable method. FEE characteristics of hBN-DNR display a low turn-on field of 6.0 V μm −1, a high field enhancement factor of 5870 and a high life-time stability of 435 min. Such an enhancement in the FEE properties of hBN-DNR derives from the distinctive material combination, i.e., high aspect ratio of the heterostructure, good electron transport from the DNR to the hBN nanowalls and efficient field emission of electrons from the hBN nanowalls. The prospective application of these heterostructures is further evidenced by enhanced microplasma devices using hBN-DNR as a cathode, in which the threshold voltage was lowered to 350 V, affirming the role of hBN-DNR in the improvement of electron emission.